Cross-Sectioning Sustainable Supply Chain Governance: A Bibliometric Analysis - Venkatarman, Anirudh; Rajkumar, A. Dunstan (International Review of Management and Marketing, 2024)
Sustainable supply chain governance is pivotal in modern business, addressing global supply chains' profound environmental, social, and ethical impacts. It necessitates establishing and administering policies to guide sustainable practices, ensuring adherence to the supply chain's environmental, social, and ethical standards. Effective governance aligns and supports business operations with sustainability goals, fostering transparency, accountability, and responsible practices. This framework guides decision-making, mitigates risks, and enhances overall supply chain resilience, contributing to a more sustainable and ethically responsible business landscape. The corporate shift towards sustainable supply chain management(SSCM) is manifested by the emerging literature documenting comprehensive changes in governance. A bibliometric-based systematic review of 128 Scopus-indexed documents (2014-2023) reveals four interconnected themes: SSCM, Sustainable Business & Operations Management, Global value chains, and Supply chain risk management. Analysis highlights the critical role of governance mechanisms in driving positive social, ecological, and economic outcomes. Governance achieves this by establishing clear policies and standards for social and environmental responsibility and ensuring robust mechanisms for compliance and accountability. Sustainable supply chain governance provides a blueprint for integrating sustainability. It ensures ongoing commitment and accountability, fostering significant and lasting positive effects on society, the environment, and overall supply chain resilience.